2023
DOI: 10.1094/pdis-07-23-1435-pdn
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Alternaria alternata and A. tenuissima Causing Black Rot in Cherry Fruits (Prunus avium) in Central Chile

Sebastián Cancino,
Mauricio Lolas,
Liszoe Galdós
et al.

Abstract: During the harvest of 2020 and 2021, sweet cherry (Prunus avium) fruit showed a firm rot with irregular pale to dark brown lesions on the fruit surface, with green to light brown fungal growth resembling Alternaria-like infection (Simmons, 2007). Diseased cherries (n= 80 fruit) were collected at harvest in mature (over 10-year-old) commercial orchards of cherry tree varieties Lapins, Regina, Santina, Skeena, and Sweetheart planted in four localities of the regions O´Higgins (33°59´ S, 70°42´W; San Francisco de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Keissl. was recently reported on cherries in Chile [9] and in China [8,10]. A. alternata is also associated with brown to black spots on cherry leaves [24,25].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Keissl. was recently reported on cherries in Chile [9] and in China [8,10]. A. alternata is also associated with brown to black spots on cherry leaves [24,25].…”
Section: Introductionmentioning
confidence: 88%
“…Sweet cherries are highly perishable fruit, with a shelf life of 7-14 days [3] and they are susceptible, during cold storage, to decay caused by postharvest pathogens, including Monilinia spp., agent of brown rot; Botrytis cinerea, agent of gray mold; Penicillium expansum, agent of blue mold; and Rhizopus spp., agent of soft rot [4][5][6][7]. Cherry production could be threatened also by black rot caused by Alternaria species, which is emerging as a major fungal disease [8][9][10]. Symptoms of black rot of Alternaria appear as dark brown to black patches on the outer surface of fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The two isolates caused the same symptoms when inoculated on young fruits of sweet cherry as that in the field, labeled as ScSs1 and ScSs2 (Figure 1D,E). [14,[21][22][23][24]. B. cinerea and M. fructicola were also identified to cause fruit rot in cherries in China [25,26].…”
Section: Isolation and Identification Of Pathogen From Diseased Fruit...mentioning
confidence: 99%
“…They occur throughout the whole fruit development period, from the young fruit stage to the post-harvest stage. Several pathogenic fungi have been reported to cause fruit rot in California, Oregon, Maryland, of the USA, and Santiago, O’Higgins, Maule, of Chile, including Monilinia fructicola , Botrytis cinerea , Sclerotinia sclerotiorum , and Alternaria alternata , which are all important pathogens in agricultural production [ 14 , 21 , 22 , 23 , 24 ]. B. cinerea and M. fructicola were also identified to cause fruit rot in cherries in China [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria alternata and Alternaria tenuissima in central Chile (Cancino et al, 2023) and Alternaria arborescens species complex (AASC) and A. alternata in Italy (Waqas et al, 2023) have been identified as the causal agents of black rot disease in sweet cherries based on the morphological and molecular analyses. These causal agents significantly contribute to yield losses.…”
Section: Introductionmentioning
confidence: 99%